The Circle of Explanation in the Sciences - í“ Nualláin, Seán (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Ontological discontinuities have logical and computational consequences. Physics with constraints begets chemistry; naí¯ve nanotechnology chose to ignore the effects of numerical constraints in orbitals on the type of molecules that can be created. On entering the biological realm, these numerical constraints begin to transform into syntax and semantics. Such projects as the HGP and GWAS have plateaued after ignoring these constraints, best handled in new subjects like biosemiotics. In this paper, a new way of parsing nature, one that starts from the fact of ontological distinctions, is proposed. Two foci are later identified; the bridge subject of biosemiotics, which this author dealt with in a previous C+H paper, and the quantum mind hypothesis. The latter is seen as another bridge, this time from the academy to the real world in which we are objects as much as subjects. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>